2017
DOI: 10.3892/mmr.2017.6996
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers and therapeutic targets for human IgA nephropathy and hypertensive nephropathy by bioinformatics analysis

Abstract: In order to further elucidate the potential correlations and treatments of IgA nephropathy (IgAN) and hypertensive nephropathy (HT), bioinformatics analysis of IgAN and HT was performed. The mRNA expression profiles of human renal biopsy samples from patients with IgAN, patients with HT and pre-transplant healthy living controls (LD) were downloaded from the Gene Expression Omnibus database. Then, the differentially expressed genes (DEGs) were identified and functions of DEGs were analyzed. Finally, the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Re-analyzing and integration of omics-based expression profiles could be an advantageous tactic to catch a holistic view of the involving genes and miRNAs in the IgAN pathogenesis. Until now, several re-analyzes have been performed on the IgAN related expression profiles, mostly on kidney tissue samples of the patients [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Re-analyzing and integration of omics-based expression profiles could be an advantageous tactic to catch a holistic view of the involving genes and miRNAs in the IgAN pathogenesis. Until now, several re-analyzes have been performed on the IgAN related expression profiles, mostly on kidney tissue samples of the patients [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…To fully explain kidney damage in IgAN, it is necessary to fully understand the effects of TLR4 in the development of glomerulopathy, involving both glomerular cells and circulating leukocytes. Studies have shown that the administration of LPS activates TLR4 receptors on mesangial cells, and causes the release of chemokines (CXCs), which promotes neutrophil infusion and the development of glomerulonephritis [114][115][116]. In addition, the IFN-γ and IFN-α responses induced by TLR activation induce overexpression of the B-cell activation factor (BAFF) in dendritic cells, favoring the expansion of B-cells and increasing IgA synthesis [117][118][119][120][121].…”
Section: Iga Nephropathy (Igan)mentioning
confidence: 99%
“…Re-analyzing and integration of omics-based expression pro les could be an advantageous tactic to catch a holistic view of the involving genes and miRNAs in the IgAN pathogenesis. Until now, several reanalyzes have been performed on the IgAN related expression pro les, mostly on kidney tissue samples of the patients [25][26][27][28]. As far as we know, there are just one experiment conducting a meta-analysis study seeking for DEGs in the PBMCs of IgAN patients.…”
Section: Discussionmentioning
confidence: 99%